Divergence and Convergence in education and work - Jorgensen, Christian Helms [Mitarbeiter]; Aarkrog, Vibe [Mitarbeiter]; Deissinger, Thomas [Mitarbeiter]; Gonon, Philipp [Mitarbeiter]; Kraus, Katrin [Mitarbeiter]; Cort, Pia [Mitarbeiter]; Phuong-Mai, Nguyen [Mitarbeiter]; Terlouw, Cees [Mitarbeiter]; Pilot, Albert [Mitarbeiter]; Weil, Markus [Mitarbeiter]; FitzSimons, Gail E. [Mitarbeiter]; Tanggaard, Lene [Mitarbeiter]; et al. (Lang, 2008)
"Are the educational systems in Europe becoming more similar or more different? This book deals with the issue of divergence and convergence in relation to systems, learning environments, and learners in vocational educational training (VET). 18 VET researchers from eight countries contribute to the examination of 'divergence and convergence' at three levels: At the national level this volume deals with the following questions: What are the consequences of the European policies that aim at converging the VET systems in Europe? What is the impact of globalization on the national systems? At the level of institutions the central issue concerns the relation between learning environments. What is the coherence between school-based education and learning in the work-place, and how can they connect? Finally at the third level of the learners and their identities the focus is on the role of vocational educational training in the formation of biographies and identities. The book thus covers the central issues on the agenda in relation to future vocational education." (Verlag, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 2.1 Lernformen; G 1.3.3 Bildungs- & Erwerbsbiografien; L 3 Lehr-Lern-Forschung; T 1.5 International vergleichende Berufsbildungsforschung; Berufsausbildung; Duales System; Lernort Schule; Lernen am Arbeitsplatz; Biografieforschung; Lerntheorie; Emotionalität; Internationaler Vergleich; Vergleichende Berufsbildungsforschung